Keanekaragaman Jenis Vegetasi Strata Semak di Hutan Perlindungan Kawasan Bukit Cogong - Destien Atmi Arisandy; Merti Triyanti (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2018)
The research aims at (1) finding the diversity index (H') of bushes vegetation stratum, and (2) abiotic environment factors at Cogong hill. This research used plotless method with Point Centered Quarter Method by classifying into three scopes, namely, research scope A, B and C with 10 items each. Based on the result, the diversity index average (H') of bushes vegetation stratum at Cogong hill in research scope A was 2,13; scope B was 1,77 and scope C was 1,61. The air temperature at Cogong hill was between 28,30C-300C, the air humidity was between 86 % - 93 %, the soil temperature was between 27,30C-29,60C, the soil humidity was between 8% - 17 % and the soil scale of acidity (pH) was between 6,3-6,7. In conclusion, the average of H' in scope A, B, and C was in medium-abundant category. Keywords : diversity , bushes stratum, protected forests, cogong hill